The Effectiveness of E-Learning Madrasah in Teaching Reading toward Students' Reading Achievement in MTsN 2 Kota Kediri - Erwin Hari Kurniawan; Angga Putra Pradana Eriantara (ELT-Lectura, 2021)
The purpose of this research was to describe the effectiveness of using E-learning Madrasah in teaching reading. This research was conducted using a descriptive quantitative approach, precisely the experimental method and the technique was used in data collection was a posttest-only control design. This research conducted to find out is there any significant different in student’s reading achievement between the experimental class and the control class. This research was conducted on 7th grade students of MTsN 2 Kota Kediri. The researcher used two classes, namely class 7I as an experimental class with a total of 35 students, and class 7J as a control class with a total of 36 students. The instrument that used was posttest and the data were analyzed by T-Test. The result of this research indicates that the student's English reading achievements in the experimental class has the mean score 80,00 which is categorized as GOOD based on the categorization table, the student's English reading achievements in the control class has the mean score 69,17 which is categorized as GOOD based on the categorization table, and the result of T-Test show that t = 3,740, df = N-2 (71-2 = 69), Sig.(2-tailed) = 0,000, and 95% confidence interval ranging from 16,612 to 5,054. The Sig.(2-tailed) is lower than 5% (0.000< 0.05), it can be concluded that there is significant difference between the experimental class and the control class.